2015
DOI: 10.1017/jfm.2014.715
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of a turbulent jet impinging on a heated wall

Abstract: Direct numerical simulation (DNS) of an impinging jet flow with a nozzle-to-plate distance of two jet diameters and a Reynolds number of 10 000 is carried out at high spatial resolution using high-order numerical methods. The flow configuration is designed to enable the development of a fully turbulent regime with the appearance of a well-marked secondary maximum in the radial distribution of the mean heat transfer. The velocity and temperature statistics are validated with documented experiments. The DNS data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 51 publications
13
56
0
Order By: Relevance
“…The authors provided turbulence statistics of the velocity and temperature, turbulent heat fluxes, local Nusselt numbers, budget terms of turbulent kinetic energy among other turbulent quantities. Recently, DNS of impinging jet flows at Re = 10,000 and Re = 8000 were performed with high spatial resolution and high order numerical methods by Dairay et al [27] and by Wilke and Sesterhenn [28], respectively. The first study focused on the role of unsteady processes to explain the spatial distribution of the heat transfer coefficient at the wall, while the latter analyzed the influence of Mach number, Reynolds number and ambient temperature on the mean velocity and temperature fields.…”
Section: Introductionmentioning
confidence: 99%
“…The authors provided turbulence statistics of the velocity and temperature, turbulent heat fluxes, local Nusselt numbers, budget terms of turbulent kinetic energy among other turbulent quantities. Recently, DNS of impinging jet flows at Re = 10,000 and Re = 8000 were performed with high spatial resolution and high order numerical methods by Dairay et al [27] and by Wilke and Sesterhenn [28], respectively. The first study focused on the role of unsteady processes to explain the spatial distribution of the heat transfer coefficient at the wall, while the latter analyzed the influence of Mach number, Reynolds number and ambient temperature on the mean velocity and temperature fields.…”
Section: Introductionmentioning
confidence: 99%
“…WSS patterns have been demonstrated to affect the heat transfer in impinging jets. As examples, the heat transfer coefficient has been shown to have similar distribution as WSS with a phase shift (Hadžiabdić & Hanjalić 2008), and Dairay et al (2015) showed that the secondary vortex resulting from flow impingement creates negative WSS regions that correspond to heat transfer augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The outlet boundary is placed at a sufficiently large radial distance, so that the error from applying the outlet-pressure condition will not affect the region of interest. According to Dairay et al [17], the radial expansion of the flow domain was chosen at 12 . The mesh has 198000 cells, and was built with special attention in the region close to the impingement plate, where a further refinement was done.…”
Section: Numerical Studymentioning
confidence: 99%